PENDIDIKAN BERBASIS MASYARAKAT DI PONDOK PESANTREN - Nurhattati Fuad (Jurnal Manajemen Pendidikan, 2012)
This research tries to elaborate and analyse the dynamic growth of pondok pesantren (pontren) Al Ittifaq, Bandung West Java as a religiously-based educational institution. In a detail, the research elaborates "how commmunity based education (CBE) implemented in al Ittifaq pontren", focusing on: 1) the objective condition of the CBE implemented in the pontren which covers autonomy of pontren, its curriculum and learning strategy carried out, empowers the community for the sake of their economic development and the community involvement, or participation, (2) managerial characteristics of CBE implemented, deals with its planning, organization, leadership, and control used in the pontren, (3) development of community-based education in pontren. With the qualitative approach by using a single case method, the writer highlights some findings as follows. First, pontren Al Ittifaq is a CBE institution in which it has certain characteristics, namely: (a) kyai-based education autonomy, (b) local need and community based-curriculum, (b) improving the community life quality through community empowering programs, and (c) developing a symbiotic mutualism model of participation, Second, there are some managerial characteristics of the CBE developed in the pontren Al Ittifaq: (a) Kyai has a dominant authority in the case of formulating and establishing the vision, mission, orientation, objective and policies of the Pontren, (b) developing the professional and familism-based organization which is carried out by building the synergic collaboration amongst Kyai, Government (both local and central), higher education institution, non-governmental organisation, companies, and local community, (c) applying the charismatic-professional leadership model, (d) implementing the internal controll based on the principles of trust, amanah, and God’ blessing. Third, CBE model in the pontren is potentially developed extensively.